2021
DOI: 10.1158/0008-5472.can-20-1777
|View full text |Cite
|
Sign up to set email alerts
|

USP24 Is a Cancer-Associated Ubiquitin Hydrolase, Novel Tumor Suppressor, and Chromosome Instability Gene Deleted in Neuroblastoma

Abstract: Deubiquitinating enzymes are increasingly recognized to play important roles in cancer, with many acting as oncogenes or tumor suppressors. In this study, we employed a bioinformatics approach to screen for enzymes from this family involved in cancer and found USP24 as a potent predictor of poor outcomes in neuroblastoma, an aggressive childhood cancer. USP24 resides in a region commonly deleted in neuroblastoma, yet was independently associated with poor outcomes in this disease. Deletion of Usp24 in a murine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As an ubiquitin‐specific protease, USP24 plays an important role in many diseases 17,20,35–37 . We explored its role in GC, and found that USP24 is highly expressed in GC, and the high expression of USP24 is closely related to the prognosis of GC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an ubiquitin‐specific protease, USP24 plays an important role in many diseases 17,20,35–37 . We explored its role in GC, and found that USP24 is highly expressed in GC, and the high expression of USP24 is closely related to the prognosis of GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As an ubiquitin‐specific protease, USP24 plays an important role in many diseases. 17 , 20 , 35 , 36 , 37 We explored its role in GC, and found that USP24 is highly expressed in GC, and the high expression of USP24 is closely related to the prognosis of GC patients. In terms of its mechanisms, USP24 enhances the stability of PLK1 through deubiquitination and upregulates the glycolysis of cells, thus promoting the pathological process in GC.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was remarkably increased in the FRG mutation group than in the non-mutation group. High-mutation frequency genes, such as FRGs like HERC2 and USP24, have been linked to the onset and progression of various malignancies [ 62 65 ]. However, the relevance of these genes to LIHC needs to be explored in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our screen focussed on the gene family encoding de-ubiquitinating enzymes (DUBs) – as these are emerging as novel therapeutic targets. When examining the impact of 95 DUBs on outcomes in NBL, we found that reduced expression of USP24 had the largest impact on outcomes, with a z-score of -10.14 (0.38 percentile) suggesting that USP24 reductions have a powerful negative impact in this disease ( 67 ). For comparison, the canonical NBL oncogene MYCN has a z-score of +8.18 (97.34 percentile) - in line with the known relationship between high expression and aggressive disease.…”
Section: Usp24 : a Cin Gene Associated With Poor Outcomes In...mentioning
confidence: 98%
“…USP24 is encoded on chromosome 1p32.3 – and area of the genome that is frequently lost in neuroblastoma tumors ( 68 , 69 ). It is notable then, that cells lacking USP24 have a significant increase in erroneous mitosis, with a particular increase in lagging chromosomes ( 67 ). These cells and tissues from mice missing even 1 copy of the Usp24 gene have a significant increase in numerical chromosome aneuploidy.…”
Section: Usp24 : a Cin Gene Associated With Poor Outcomes In...mentioning
confidence: 99%